Formulasi dan Uji Aktivitas Antioksidan dengan Metode DPPH dari Minuman Sari Buah Cempedak (Artocarpus Integer) Menggunakan Spektrofotometri UV-Vis - Sumardi, Sumardi; Zebua, Nilsya Febrika; Ulpah, Ulpah (Journal of Pharmaceutical and Health Research, 2024)
As chempedak fruit is only used fresh in the community, it is easily affected by mechanical, chemical, and microbiological factors and decays quickly. Therefore, fruit processing becomes very important to extend the shelf life of the fruit. Making juices, syrups, and juice products with a long shelf life is one of the selected ways of fruit utilization. The preparation of cempedak fruit juice as an antioxidant is the objective of this study. This is a summary of the article to help the reader quickly ascertain the purpose of the study according to the research needs. Fruit juice is a drinkable liquid obtained by squeezing or filtering the pulp. Cempedak juice drink formulas were tested for antioxidant activity in water, sugar, and CMC as part of the formula optimization process using SLD (simple lattice design) and respondent polling. Seven cempedak juice drink formulas with concentrations of 80 µg/mL, 60 µg/mL, 40 µg/mL, and 20 µg/mL were shown to have antioxidant capacity based on the results. The IC50 readings of the seven cempedak juice drink formulas are as follows: 7.948 µg/mL, 2.048 µg/mL, 3.085 µg/mL, 0.435 µg/mL, 11.057 µg/mL, 3.388 µg/mL, and 2.726 µg/mL, all of which were considered very strong. The audience found high popularity in the optimal formula made with a mixture of water, sugar, and CMC addition in the hedonic test, which measured responses to taste, aroma, and color. The highest pH of 4 was achieved in the pH 7 test of the Cempedak juice drink recipe. The homogeneity and cycling test results showed that the beverage formulation could be integrated into the drink.